Traditional Use of Medicinal Plants in Baturraden, Central Java - Nofrianti Nofrianti; Wahyu Utaminingrum; Dwi Hartanti (Jurnal Jamu Indonesia, 2021)
An ethnopharmacological study is an initial step for the development of jamu, which has been simultaneously conducted throughout Indonesia. This study aimed to explore the utilization of medicinal plants in Baturraden, a region with relatively rich plant biodiversity in Java. Our research is a quantitative ethnobotanical study reporting the utilization of medicinal plants as a single plant botanical preparation in the studied area. The data were collected through semi-structured interviews with 36 informants on the local names, indications, parts used, method of preparation, and application of the plants. The species use-value (SUV), relative frequency citation (RFC), and the fidelity level (FL) of each species were calculated accordingly. The study recorded the utilization of 47 species of medicinal plants, which were employed to treat 32 ailments. Leaves, decoctions, and oral were recorded as the most commonly used plant part, herbal preparation, and application. There were 24 botanical preparations with the FL value of 100%, which were indicated for the treatment of fourteen diseases/symptoms. Curcuma longa, Zingiber officinale, Piper betle, Cymbopogon citratus, Andrographis paniculata, Syzygium polyanthum, Citrus aurantiaca, and Zingiber montanum were considered as the most important and valuable plants by the local community. Hence, those plants should be evaluated further for their pharmacological activity and developed into standardized botanical preparations.